Theoretical bases of concept development transmedia storytelling - Yessenbekova У.М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The article explores the concept of transmedia storytelling and ways to use transmedia in modern media space. Analyzed its role in the improvement of information technology and media systems. Theoretical concepts and principles of transmedia are considered, the stages of its use in the information and communication environment are revealed. The recommendations for improving the information and communication potential of society. The article systematizes and studies the problems of transmedia technologies and the importance of transmedia strategies, its influence on the audience, the social aspects of interactive media. The author used different methodologies for determining and predicting transmedia processes. The article was written with the aim of developing transmedia storytelling, taking into account the peculiarities of the domestic media market, the use of transmedia forms to preserve national identity, human development and society.